Addressing financial biases in university undergraduates: Unveiling connections with knowledge, behaviours and attitudes - Celia López-Penabad; Marcos Álvarez-Espiño; Leandro Benito-Torres (PLoS ONE, 2025)
Purpose This study investigates how financial knowledge, behaviours, and attitudes shape the prevalence of financial biases among Economics students at the University of Santiago de Compostela. Methodology Based on survey data from 403 first- and fourth-year students, a composite bias index—covering overconfidence, gambler’s fallacy, and herd behaviour—is constructed using the Benefit of the Doubt method. Truncated regressions explore the influence of financial capability. Findings Results show attitudinal factors explain biases better than knowledge. Surprisingly, behaviours such as long-term planning and fraud avoidance increase susceptibility to biases. These findings highlight the complexity of financial decision-making and the need for emotionally aware, bias-targeted financial education. Value This paper introduces a novel approach by constructing multiple financial bias indices and calling for hands-on, behaviour-focused financial education.